2005
DOI: 10.1158/0008-5472.can-04-3544
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Pollutant and Potent Mutagen 3-Nitrobenzanthrone Forms DNA Adducts after Reduction by NAD(P)H:Quinone Oxidoreductase and Conjugation by Acetyltransferases and Sulfotransferases in Human Hepatic Cytosols

Abstract: 3-Nitrobenzanthrone (3-nitro-7H-benz [de]anthracen-7-one, 3-NBA) is a potent mutagen and suspected human carcinogen identified in diesel exhaust and air pollution. We compared the ability of human hepatic cytosolic samples to catalyze DNA adduct formation by 3-NBA. Using the 32 P-postlabeling method, we found that 12/12 hepatic cytosols activated 3-NBA to form multiple DNA adducts similar to those formed in vivo in rodents. By comparing 3-NBA-DNA adduct formation in the presence of cofactors of NAD(P)H:quinone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
164
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(177 citation statements)
references
References 45 publications
12
164
1
Order By: Relevance
“…Previously, we detected the formation of 3-NBAderived DNA adducts in rodent tissues by 32 P-postlabeling, all of which are derived from reductive metabolites of 3-NBA bound to purine bases, but structural identification of these adducts has not yet been reported. We have now prepared 3-NBA-derived DNA adduct standards for -ABA in two independent systems (thin layer and high-performance liquid chromatography).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we detected the formation of 3-NBAderived DNA adducts in rodent tissues by 32 P-postlabeling, all of which are derived from reductive metabolites of 3-NBA bound to purine bases, but structural identification of these adducts has not yet been reported. We have now prepared 3-NBA-derived DNA adduct standards for -ABA in two independent systems (thin layer and high-performance liquid chromatography).…”
mentioning
confidence: 99%
“…9 Its genotoxicity has been further documented by the detection of specific DNA adducts formed in various chemical and enzymatic in-vitro assays, in cells and in vivo in rodents treated with 3-NBA. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] The main metabolite of 3-NBA, 3-aminobenzanthrone (3-ABA, Fig. 1), has been found in urine samples of underground salt mine workers occupationally exposed to diesel emissions, 10 and this metabolite forms the same DNA adducts as those formed by its nitroaromatic counterpart 3-NBA.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the authors used the HRN (Hepatic Cytochrome P450 Reductase Null) mouse model, previously shown to be suitable for examining hepatic versus extrahepatic xenobiotic metabolism in vivo [48][49][50][51] . For this reason , we have advocated this animal model for elucidating AA metabolism 25 .…”
Section: The Role Of Biotransformation Enzymes In the Development Of mentioning
confidence: 99%